The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1039/c6gc01483f
|View full text |Cite
|
Sign up to set email alerts
|

A method for simultaneous bioflocculation and pretreatment of algal biomass targeting improved methane production

Abstract: A novel method for simultaneous bioflocculation and pretreatment of algae is revealed. The method includes bioflocculation of precultured algae (Chroococcus sp.) using pellet forming filamentous fungus (Aspergillus lentulusFJ172995) resulting in nearly 100% harvesting within 6 h without addition of any nutrient and carbon source at the optimized fungal/algal (F/A) ratio of 1:3. The algal-fungal interactions require metabolically active fungus with opposite charge. The bioflocculation process is replicable at r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…The present study can be closely related to the above-mentioned cases as it also reports extracellular secretions from A. fumigatus , mediating cell wall changes in the C. pyrenoidosa cells. These secretions might help A. fumigatus to provide signal to the C. pyrenoidosa cell and bring it into close vicinity for nutritional benefits or enzymatic degradation [32]. Similar phenomenon of microalgal–fungal attachment has been reported by our group with wide range of microalgal species encompassing green algae ( Chlorella sp.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…The present study can be closely related to the above-mentioned cases as it also reports extracellular secretions from A. fumigatus , mediating cell wall changes in the C. pyrenoidosa cells. These secretions might help A. fumigatus to provide signal to the C. pyrenoidosa cell and bring it into close vicinity for nutritional benefits or enzymatic degradation [32]. Similar phenomenon of microalgal–fungal attachment has been reported by our group with wide range of microalgal species encompassing green algae ( Chlorella sp.…”
Section: Discussionsupporting
confidence: 62%
“…Apart from biodiesel aspect, harvesting of microalgae using filamentous fungi also increases its biogas potential. Prajapati et al [32] reported enhanced bio-methane production from algal–fungal pellets due to the enzymatic degradation of microalgal cell wall by the fungi. All these studies show that harvesting algae with filamentous fungi is a favorable process for biofuel production.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, algal-fungal copelletization improved oil extraction efficiency because fungal secreted hydrolytic enzymes disrupted the thick cell walls of Tetraselmis suecica (Muradov et al, 2015). The same was seen between Aspergillus lentulus FJ172995 and Chroococcus sp., where algal and fungal cells formed a pellet, and nearly 100% of biomass settled down within 6 h at an optimized fungal/algal ratio of 1:3 (Prajapati et al, 2016).…”
Section: Downstream Processing Of Algal Biomass Using Symbiontsmentioning
confidence: 99%